Selective targeting of NRF2-high pancreatic ductal adenocarcinoma with an NQO1-activatable prodrug - Laura Antonucci; Kosuke Watari; Yechen Feng; Jingjing Qi; Mandy Zhu; Tingya Wang; Isabella Ng; Emily A. Vucic; Irene Riahi; Li Huang; Mojgan Hosseini; Evangeline Mose; et al. (Proceedings of the National Academy of Sciences, 2026)
Activation of transcription factor NRF2 in pancreatic ductal adenocarcinoma (PDAC) promotes aggressive tumor phenotype and protection from therapy-induced oxidative stress. We postulated that NRF2 high PDAC can be selectively targeted by C29h, a prodrug that is activated by the NRF2-induced enzyme NAD(P)H:quinone oxidoreductase-1 (NQO1), which is elevated in human pancreatic tumors. Initial evaluations of C29h alone or together with the standard-of-care chemotherapeutic drug gemcitabine were conducted on NQO1 high human and mouse PDAC cell lines and patient-derived organoids. As PDAC is enriched in collagen-containing extracellular matrix (ECM) that activates NRF2 and induces NQO1 expression, we examined the ECM effect on the response to C29h, as well as in vivo tumor control in IKKα-deficient Kras G12D /Ikkα ΔPEC mice in which NRF2 is strongly activated, immunocompromised Nu/Nu mice orthotopically transplanted with human PDAC cells and C57BL/6n and NOD/SCID mice transplanted with mouse PDAC. C29h led to NQO1-dependent killing of human and mouse PDAC cell lines and organoids and acted additively with gemcitabine. Furthermore, ECM-plated PDAC cells were more susceptible to C29h cytotoxicity than cells grown on plastic. Importantly, C29h treatment induced tumor regression and increased the survival of PDAC-bearing mice and optimal C29h-induced tumor regression was dependent on CD8 + T lymphocytes whose tumoral recruitment was enhanced by drug treatment. This study supports the use of C29h alone or as part of a drug combination as an effective and promising strategy for selective eradication of NRF2 high PDAC.